The Relevance of Blended Learning to Students' Critical Thinking Skills - Miftah Faridli, Efi (Newinera Publisher, 2025)
This research examines how blended learning affects students' ability to think critically. This kind of quantitative study uses A design for a time series and a Semi-Experimental method. This During the odd semester of 2023–2024, research was done at a Public Junior High School in Banyumas Regency. A total of 35 students were selected from two classes to be used as research samples. Essay questions, critical thinking variable surveys, Using HOTS in blended learning techniques, as well as field notes are the tools used. The research findings show that students' critical thinking skills increased when the blended learning approach is combined with the HOTS strategy. This conclusion is supported by the results of the ANOVA analysis, which shows an F value of 6.253 at a level of significance of 0.039. Because the calculated F exceeds the F table, The suggested hypothesis's findings are acknowledged. Specifically, 6.253> 4.196. The study's findings demonstrate that pupils' critical thinking abilities improve when the blended learning model and the HOTS approach are used simultaneously.